I can't save you : a memoir - Chin-Quee, Anthony (Riverhead Books, 2023)
"The raw and gripping memoir of a Black physician who confronts his past mistakes and relationships as he learns to find his own path forward At first glance, Anthony Chin-Quee looks like a traditional success story: a smart, ambitious kid who grew up to become a board-certified otolaryngologist--an ear, nose, and throat surgeon. Yet the truth is more complicated. As a self-described "not white, mostly Black, and questionably Asian man," Chin-Quee knows that he doesn't fit easily into any category. Growing up in a family with a background of depression, he struggled with relationships, feelings of inadequacy, and a fear of failure that made it difficult for him to forge lasting bonds with others. To repair that, he began his own unflinching examination of what it means to be both a physician and a Black man today. What saved him and his sanity was not medicine but storytelling: by sharing stories from his life and career, Chin-Quee learned how powerful the truth can be in helping to forgive yourself and others as you chart a new way forward. By turns harrowing and hilarious, honest and human, I Can't Save You is the fascinating true story of how looking within can change you and your life for the better"--